A Classification of a Totally Umbilical Slant Submanifold of Cosymplectic Manifolds. (29th February 2012) - Uddin, Siraj; Ozel, Cenap; Khan, Viqar Azam
Abstract : We study slant submanifolds of a cosymplectic manifold. It is shown that a totally umbilical slant submanifold M of a cosymplectic manifold M ̅ is either an anti-invariant submanifold or a 1−dimensional submanifold. We show that every totally umbilical proper slant submanifold of a cosymplectic manifold is totally geodesic.